The effect of thermoelectric craniocerebral cooling device on protecting brain functions in post-cardiac arrest syndrome - Nadir, Aydın; Kara, Deniz; Turkoz, Ayda (Frontiers in Cardiovascular Medicine, 2025)
AimThis study aimed to protect brain functions in patients who experienced in-hospital cardiac arrest through the application of local cerebral hypothermia. By utilizing a specialized thermal hypothermia device, this approach sought to mitigate ischemic brain injury associated with post-cardiac arrest syndrome, enhance survival rates, and improve neurological outcomes as measured by standardized scales.MethodsA prospective, single-center cohort study was conducted involving patients aged ≥18 years who experienced in-hospital cardiac arrest and achieved return of spontaneous circulation (ROSC). Patients were cooled using a hypothermia helmet to achieve a target temperature of 32°C–34°C, maintained for 36–72 h, followed by controlled rewarming and normothermia for 72 h. Neurological recovery was assessed using the Cerebral Performance Category (CPC) scale, where CPC 1–2 denotes good recovery and CPC 3–5 indicates poor outcomes. Body temperature, hemodynamic parameters, biochemical changes, and survival data were meticulously recorded and analyzed. Statistical analysis included paired t-tests to compare pre- and post-treatment data.ResultsOf 116 cardiac arrest cases, 30 (25.86%) were in-hospital, and 16 (53.33%) of these achieved ROSC. Among the patients, 62.5% underwent emergency coronary angiography due to ST-elevation myocardial infarction (STEMI). The mean time to hypothermia initiation was 32.9 ± 13.5 min, with hypothermia maintained for 58 ± 6.4 h. Neurological outcomes were favorable, with 62.5% of patients achieving CPC scores of 1 or 2, indicating functional recovery and independence. In contrast, CPC scores of 3 or higher were observed in 37.5% of patients, reflecting varying degrees of disability. Biochemical analysis revealed significant decreases in sodium, potassium, calcium, and magnesium levels, alongside increased urea and creatinine concentrations. Hemodynamic improvements included elevated systolic blood pressure and heart rate, while left ventricular ejection fraction remained stable. Overall survival was 75%, and the majority (62.5%) of survivors were discharged without significant neurological deficits.ConclusionThe findings suggest that early and targeted application of craniocerebral thermal hypothermia has the potential to improve survival and preserve neurological function in post-cardiac arrest syndrome. The high rates of favorable outcomes, as reflected by CPC scores, underscore the neuroprotective effects of localized hypothermia. Further large-scale, multicenter trials are recommended to validate these promising results and refine protocols for optimal clinical application.